Perfil epidemiológico dos casos de síndrome respiratória aguda grave no estado de Minas Gerais, Brasil, 2020 a 2021 - (:unkn) unknown (Universidade Brasil, 2022)
The increase in the number of cases of Severe Acute Respiratory Syndrome (SARS) associated with Sars-CoV-2 has originated one of the largest public health emergencies worldwide. This study was developed to examine the epidemiological profile of SARS in the state of Minas Gerais during 2020 and 2021. A cross-sectional, descriptive, retrospective, and qualitative-quantitative investigation was carried out using the state of Minas Gerais as the unit of analysis. Data were collected from the SIVEP-Gripe (Flu) system and the COVID-19 Case Monitoring Panel, for the years 2020 and 2021. The following variables were analyzed: total COVID-19 cases, total SARS and SARS due to COVID-19, age, gender, race, final classification, and evolution outcome. The data were entered in a spreadsheet, analyzed, and published in the form of graphs, tables, and graphs. The state had 315,726 cases of SARS, of which 58.6% were caused by Sars-CoV-2. Most individuals who had SARS were male (53.2%), aged over 60 years (50.9%), and mixed-race (45.4%). Among the SARS cases, 23.3% evolved to death, and, of these, 77.6% had COVID-19 as the underlying cause. The regions of Uberlândia, Belo Horizonte, Coronel Fabriciano, Patos de Minas, Uberaba, Ituiutaba, Leopoldina, Governador Valadares, and Juiz de Fora had the highest occurrences of SARS/1000 inhabitants. The regions of São João Del Rei, Teófilo Otoni, Passos, and Uberaba stood out with a high lethality rate of patients who had SARS due to COVID-19. The distribution of reported SARS cases and deaths in Minas Gerais was heterogeneous, with a greater number of cases occurring in municipalities with higher population density. The questions presented in this study revealed the deficiencies, weaknesses, and diversities in the response capacities to face the pandemic, suggesting the need for decentralization and restructuring of the health system of several municipalities in the state.
Keywords: COVID-19; Epidemiologia descritiva; Sars-Cov-2; SRAG; CB